2006
DOI: 10.1142/s0217984906012018
|View full text |Cite
|
Sign up to set email alerts
|

Coherent Pair Production in Deformed Crystals With a Complex Base

Abstract: We investigate the coherent electron-positron pair creation by high-energy photons in a periodically deformed single crystal with a complex base. The formula for the corresponding differential cross-section is derived for an arbitrary deformation field. The conditions are specified under which the influence of the deformation is considerable. The case is considered in detail when the photon enters into the crystal at small angles with respect to a crystallographic axis. The results of the numerical calculation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 9 publications
1
48
0
Order By: Relevance
“…Of particular interest is the Sivers [12] function, entering in the transverse target spin asymmetry, because of its link to the quark orbital angular momentum [13], the main still unmeasured contribution to the nucleon spin. Measurements of multiplicities and double spin asymmetries as a function of the final transverse momentum of pions [14,15] suggest that transverse momentum distributions may depend on the polarization of quarks and possibly also on their flavor. This is also pointed out by the different behavior of the Collins and Sivers asymmetries measured on the neutron [16] with respect to the proton results from Hermes [17,18].…”
Section: Tmd Results At Jlabmentioning
confidence: 99%
“…Of particular interest is the Sivers [12] function, entering in the transverse target spin asymmetry, because of its link to the quark orbital angular momentum [13], the main still unmeasured contribution to the nucleon spin. Measurements of multiplicities and double spin asymmetries as a function of the final transverse momentum of pions [14,15] suggest that transverse momentum distributions may depend on the polarization of quarks and possibly also on their flavor. This is also pointed out by the different behavior of the Collins and Sivers asymmetries measured on the neutron [16] with respect to the proton results from Hermes [17,18].…”
Section: Tmd Results At Jlabmentioning
confidence: 99%
“…In the presence of acoustic waves we have a set of peaks specified by m. The angular distance between them is of the order (ω s /ω)(c/v s ). The radiation intensity at the peaks is given by expressions (30) and (31). The angular-frequency parameters of the peaks can be controlled by tuning the amplitude and the wavelength of the ultrasound.…”
Section: Resultsmentioning
confidence: 99%
“…From the point of view of controlling the parameters of various radiation processes in a medium, it is of interest to investigate the influence of external fields, such as acoustic waves, temperature gradient etc., on the corresponding characteristics. The considerations of processes, such as diffraction radiation, 20,21 parametric Xradiation, 22 channeling radiation, [23][24][25][26][27][28][29] bremsstrahlung of high-energy electrons, 30,31 electron-positron pair creation by high-energy photons, 32,33 have shown that the external fields can remarkably change the spectral and angular characteristics of the radiation intensities. Recently there has been broad interest in compact crystalline undulators with periodically deformed crystallographic planes as an efficient source of high energy photons [34][35][36][37][38][39][40][41][42][43] (for a review see Ref.…”
Section: Introductionmentioning
confidence: 99%
“…[14,16] need to be extended to include a microscopic, quark-level description of unfavored fragmentation. This would then enable predictions to be made for the angular or p T dependence of semi-inclusive pion production [19], which may reveal further insights into the hadronization process.…”
Section: Discussionmentioning
confidence: 99%